Combined Effect Of Emblica Officinalis And Tinospora Cordifolia On Hemato-Biochemical Profile Of Murrah Buffalo Calves (Applied Biological Research, 2016)
The present study was aimed to assess the performance of neonatal  buffalo calves based on haematological and biochemical profile upon  supplementation of Emblica officinalis and Tinospora cordifolia, well  known anti-anaemic, adaptogenic and anti-stressor herbs. Twelve calves  aged 14 d were randomly divided into 2 groups of 6 each. One group  was maintained as control and other group supplemented with a  combination of dry powder of E. officinalis and T. cordifolia (2:1) @ 450  mg kg-1 body weight once a day orally for 28 days. Blood samples were  collected aseptically from control and experimental animals on 28th and  42nd day age of calves from jugular vein. The treatment group showed  significantly higher (p
Keywords: Emblica officinalis; Haemato-biochemical profile; Murrah buffalo calves; Tinospora cordifolia